Effect of intravenous thrombolysis before endovascular therapy on outcome according to collateral status: insight from the ETIS Registry. (3rd February 2022) - Anadani, Mohammad; Januel, Anne-Christine; Finitsis, Stephanos; Clarençon, Frédéric; Richard, Sébastien; Marnat, Gaultier; Bourcier, Romain; Sibon, Igor; Dargazanli, Cyril; Arquizan, Caroline; Blanc, Raphael; Lapergue, Bertrand; et al.
Abstract : Background: It is unknown whether collateral status modifies the effect of pretreatment intravenous thrombolysis (IVT) on the outcomes of patients with large vessel occlusions treated with endovascular therapy (EVT). We aimed to assess whether collateral status modifies the effect of IVT on the outcomes of EVT in clinical practice. Methods: We used data from the ongoing prospective multicentric Endovascular Treatment in Ischemic Stroke (ETIS) Registry in France. Patients with anterior circulation proximal large vessel occlusions treated with EVT within 6 hours of symptom onset were enrolled. Patients were divided into two groups based on pretreatment with IVT. The two groups were matched based on baseline characteristics. We tested the interaction between collateral status and IVT in unadjusted and adjusted models. Results: A total of 1589 patients were enrolled in the study, of whom 55% received IVT. Using a propensity score matching method, 724 no IVT patients were matched to 549 IVT patients. In propensity score weighted analysis, IVT was associated with higher odds of early neurological improvement (OR 1.74; 95% CI 1.33 to 2.26), favorable functional outcome (OR 1.66; 95% CI 1.23 to 2.24), excellent functional outcome (OR 2.04; 95% CI 1.47 to 2.83), and successful reperfusion (OR 2.18; 95% CI 1.51 to 3.16). IVT was not associated with mortality or hemorrhagic complications. There was no interaction between collateral status and IVT association with any of the outcomes. Conclusions: Collateral status does not modify the effect of pretreatment IVT on the efficacy and safety outcomes of EVT.